Axial stress–strain behavior of carbon FRP-confined seawater sea-sand recycled aggregate concrete square columns with different corner radii. (15th April 2021) - Li, Pengda; Yang, Tianqi; Zeng, Qiang; Xing, Feng; Zhou, Yingwu
Abstract: This paper presents an experimental study on the axial stress–strain behavior of carbon fiber-reinforced polymer (CFRP)-confined seawater sea-sand recycled aggregate concrete (SSRAC) columns. Forty-two circular and square specimens were tested under axial compression, and the effects of the aggregate replacement ratio, CFRP thickness, and corner radius were investigated. The results indicated that, by replacing natural aggregates with recycled aggregates (RAs), the CFRP-confinement effectiveness can be enhanced, showing a higher enhancement ratio in the ultimate strength and strain. The effect of the corner radius ratio on the ultimate condition of CFRP-confined SSRAC is also more pronounced compared with CFRP confined natural aggregate concrete (NAC). This conclusion was also validated by the nonuniform hoop strain distribution for specimens with varying corner radius ratios. The difference in CFRP confinement efficiency caused by the recycled aggregate replacement and corner radius is accurately captured by the DIC (Digital image correlation) measurement system. By reasonably taking the coupling effect of RAs and the corner radius ratio into account for the confinement efficiency parameter, the proposed ultimate strength and strain model for CFRP-confined SSRAC demonstrates a satisfactory performance when compared with test results.